MEMBANGUN LITERASI KEUANGAN SYARIAH SEJAK DINI: PENGARUH KOMPETENSI GURU DAN PERAN DUKUNGAN ORANG TUA PADA SISWA SEKOLAH DASAR - Syaiful Hannas; Pungky Lela Saputri (STKIP Subang, 2026)
Islamic financial literacy is an important competency that should be instilled from an early age to develop financial behavior in accordance with Islamic principles. This study aims to analyze the effect of teachers’ competence in integrating Islamic economic values on the Islamic financial literacy of elementary school students, examine the effect of parental support on students’ Islamic financial literacy, and investigate the moderating role of parental support in this relationship. This study employed a quantitative approach using primary data collected through questionnaires distributed to fourth-, fifth-, and sixth-grade elementary school students in Semarang City, Indonesia. The sample was selected using a multistage random sampling technique. Data were analyzed using Moderated Regression Analysis (MRA). The results indicate that teachers’ competence in integrating Islamic economic values has a positive and significant effect on students’ Islamic financial literacy. Parental support also has a positive and significant effect on students’ Islamic financial literacy. Furthermore, parental support significantly moderates the relationship between teachers’ competence and students’ Islamic financial literacy by strengthening the effect of teachers’ competence. These findings suggest that the improvement of students’ Islamic financial literacy is influenced not only by the quality of learning provided by teachers but also by the active involvement of parents through financial education, guidance, and role modeling within the family environment. Therefore, effective collaboration between schools and families is essential to optimize the development of Islamic financial literacy among elementary school students.